2015
DOI: 10.1515/biolog-2015-0018
|View full text |Cite
|
Sign up to set email alerts
|

Red list of ferns and flowering plants of Slovakia, 5th edition (October 2014)

Abstract: The last version of Red List was published already more than 10 years ago but the knowledge of the flora of Slovakia has substantially improved due to large-scale mapping projects and taxonomical research. Therefore an updated fifth edition of the Red List is presented in this paper. For evaluation, we accepted IUCN categories (ER, CR, EN, VU, NT, LC, DD, NA, NE) and criteria (A-D), which were used first time in the history of Slovak Red Lists of ferns and flowering plants. In total 1 218 taxa are listed (the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(69 citation statements)
references
References 9 publications
1
64
0
4
Order By: Relevance
“…Percentage of the number of species included in RBRF, which occur in Mordovia to the total number of species included in RBRF, % management (Tomović et al 2007, Eliáš jun. et al 2015, Rossi et al 2015, Stroh et al 2014, Moreno Saiz et al 2015.…”
Section: Familymentioning
confidence: 99%
“…Percentage of the number of species included in RBRF, which occur in Mordovia to the total number of species included in RBRF, % management (Tomović et al 2007, Eliáš jun. et al 2015, Rossi et al 2015, Stroh et al 2014, Moreno Saiz et al 2015.…”
Section: Familymentioning
confidence: 99%
“…The critically endangered Orobanche elatior is a taxon with not enough data on its occurrence within Slovakia (Eliáš et al 2015). However, in older literature, it is considered as a rare taxon in the studied area, mainly in the south-east of the territory (Hlavaček 1985).…”
Section: Discussionmentioning
confidence: 99%
“…According to the actual Red List of plant species of Slovakia (Eliáš et al 2015) we identified 17 species listed in IUCN categories. The critically endangered Orobanche elatior is a taxon with not enough data on its occurrence within Slovakia (Eliáš et al 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since several historical sites have disappeared , it is included in the Slovak Red List of rare and endangered plants (Eliáš et al 2015) and protected by law (Anonymous 2003).…”
Section: Introductionmentioning
confidence: 99%